2016
DOI: 10.2142/biophysico.13.0_77
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of substrate specificities of uridine-cytidine kinase

Abstract: A uridine-cytidine kinase (UCK) catalyzes the phosphorylation of uridine (Urd) and cytidine (Cyd) and plays a significant role in the pyrimidine-nucleotide salvage pathway. Unlike ordinary ones, UCK from Thermus thermophilus HB8 (ttCK) loses catalytic activity on Urd due to lack of a substrate binding ability and possesses an unusual amino acid, i.e. tyrosine 93 (Tyr93) at the binding site, whereas histidine (His) is located in the other UCKs. Mutagenesis experiments revealed that a replacement of Tyr93 by His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The replacement of Arg152 with Leu reduced the activity towards cytidine (data not shown). These interactions between uridine and ttCK are indispensable for substrate binding, which is consistent with the molecular dynamics simulation [23] .…”
Section: Resultssupporting
confidence: 88%
“…The replacement of Arg152 with Leu reduced the activity towards cytidine (data not shown). These interactions between uridine and ttCK are indispensable for substrate binding, which is consistent with the molecular dynamics simulation [23] .…”
Section: Resultssupporting
confidence: 88%
“…To further understand the contributions of different amino acid residues to the stability of ketoenamine and enolimine tautomers at the active site of the SHMT enzyme, we carried out the energy decomposition analysis through MM‐PBSA calculations . It is found that the ARG232 residue, which is hydrogen bonded to the phosphate oxygens of the PLP ring, has most pronounced effect in stabilization of the two tautomers.…”
Section: Resultsmentioning
confidence: 99%
“…When Tyr93 was replaced by histidine (Y93H) or glutamine (Y93Q), TtCK recovered the phosphorolytic activity towards uridine. Conversely, when Tyr93 was replaced by a smaller residue, such as Phe or Leu, uridine could not be accepted by TtCK either (Tanaka et al 2016;Tomoike et al 2011) (Fig. 10).…”
Section: Nucleoside Kinases (Nks)mentioning
confidence: 99%
“…Recent studies (Tanaka et al 2016;Tomoike et al 2011) described the presence of an unusual amino acid (Tyr93) in the active site of TtCK, while in other UCKs histidine (His) is commonly found at this position. In view of this finding, the authors suggested that the strict specificity for cytidine can be attributed to this single residue.…”
Section: Nucleoside Kinases (Nks)mentioning
confidence: 99%